2020
DOI: 10.5194/isprs-archives-xliii-b3-2020-899-2020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Evaluation of Remote Sensing Indices for Agricultural Drought Monitoring Over Kazakhstan

Abstract: Abstract. Drought has a significant impact on the Kazakhstan’s agricultural economy, which is the world's largest wheat flour exporting country. Remote sensing provides an efficient tool for monitoring agricultural drought in a wide range. Hundreds of remote sensing drought indices have been developed during the past decades. Some of them have been widely used over the world as an indispensable indicator in drought monitoring systems. However, the applicability of those indices in Kazakhstan, the largest count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Following studies on the remote sensing monitoring of agricultural drought [19,27,32,33], seven widely used remote sensing indices were selected. These indexes were calculated using the MOD09A1 and MOD11A2 products.…”
Section: Methods 231 Selection Of Remote Sensing Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Following studies on the remote sensing monitoring of agricultural drought [19,27,32,33], seven widely used remote sensing indices were selected. These indexes were calculated using the MOD09A1 and MOD11A2 products.…”
Section: Methods 231 Selection Of Remote Sensing Indicesmentioning
confidence: 99%
“…Due to the complexity of the earth-atmosphere system, the diversity of organisms, and drought variability, the applicability and accuracy of remote sensing indices for drought monitoring may be affected by many factors, such as time and space, farmland environment, crop type, and different developmental stages of crops [32]. Previous studies have indicated that remote sensing indices vary significantly in different regions, and a single index may not reflect the intensity and severity of drought in different regions [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of GIS, Google Earth Engine (GEE) is an advanced cloud-based platform to process all kind of spatial data in a quick time frame (Sun et al, 2020;. The GEE will work in JavaScript and Python streamline, likewise in this study all the data have been processed in GEE through JavaScript API.…”
Section: Earth Engine Data Processingmentioning
confidence: 99%
“…It describes the reduction of water volume in rivers or reservoirs due to insufficient surface or groundwater, and examples of this type of index are the SWSI [11] and SRI [12]. The above are single-element drought indices, which can only capture specific phases of drought and may not reflect the overall trend or internal mechanisms of the process [13][14][15].…”
Section: Introductionmentioning
confidence: 99%